The Ilustration of Mental Health and Physical Activity in Adolescents - Ari Dwi Jayanti Desak Made; Gusti Ayu Putu Satya Laksmi; I Nyoman Dharma Wisnawa; I Gede Satria Astawa (Babali Health, 2023)
Introduction: Mental health is a condition in which individuals realize their potential, are able to contribute, prosper, work productively and are able to contribute to the environment. Physical activity is any body movement capable of producing energy. The purpose of this study was to determine the description of mental health and physical activity in adolescents. Methods: Quantitative descriptive research method with a cross-sectional approach. The population is 780 youths, a sample of 265 people is calculated using the slovin formula. The sampling method uses stratified random sampling. The measuring tool for mental health variables uses the SRQ-29 and physical activity uses the IPAQ. Results: The results of the study showed that 46.4% of respondents had symptoms of mental-emotional disorders, none of the respondents used psychoactive substances, 4.9% of respondents had psychotic symptoms/psychosis, 7.5% of respondents had PTSD symptoms. In the physical activity variable, most respondents had moderate physical activity, 39.6%. Conclution: The mental health problems experienced by respondents and the physical activity undertaken may be influenced by characteristics such as age, gender, relationships with colleagues, stress, bullying. Respondents are expected to pay attention to their mental health conditions and continue to carry out physical activities in their daily lives. Keywords: Adolescents , mental health, physical health.